Detecção e identificação molecular de espécies de Sarcocystis em tecidos de animais e sua importância em saúde única - Rosa, Gilneia da (2024)
The genus Sarcocystis has a worldwide distribution, with a heteroxenous life cycle, comprising three species known to be zoonotic: Sarcocystis suihominis, Sarcocystis heydorn, and Sarcocystis hominis, while Sarcocystis bertrami is reported to cause food poisoning in humans consuming raw horse meat. In Brazil, the consumption of wild boar meat has become common, as these invasive exotic fauna have legalized hunting to control their overabundance, these animals, besides acting as intermediate hosts for S. suihominis and S. miescheriana, may harbor other undocumented species. Additionally, horse meat consumption is atypical in Brazil, however, the country exports this protein to asian and european consumer markets. Nonetheless, data on the identification and occurrence of Sarcocystis spp. infecting these animals are scarce. Therefore, in article 1, we investigated the presence of Sarcocystis spp. in 108 tissue samples from 24 horses in the State of Rio Grande do Sul. Microscopic tissue cysts were observed in three tongue and esophagus samples from two animals. DNA samples from the cysts and all tissues were subjected to Nested-PCR amplifying the 18SrRNA region, followed by Restriction Fragment Length Polymorphism (RFLP) analysis using DdeI and HpaII enzymes. Sarcocystis spp. DNA was detected in 67.6% (73/108) of the samples and in 91.7% (22/24) of the sampled animals. The tissues with the highest detection frequency were the diaphragm 92.3%, (12/13), gluteal muscle 77.2%, (17/22), and esophagus 66.7%, (4/6). In the RFLP analysis, Sarcocystis spp. were detected in 21 tissues from 11/22 horses, and the cysts, identified by nucleotide sequencing, were identified as S. bertrami. S. neurona was detected in 11 samples from 7/22 animals, with coinfection in 5/22 cases. This high detection rate indicates a concerning circulation of the protozoan, especially S. bertrami, found in all tissues. Subsequently, in article 2, aiming to investigate zoonotic species and considering the importance of wild boar meat consumption in Brazil, as well as extensively raised pigs, a second study was conducted. Molecular analysis was performed on 210 samples, of which 67 were positive for Sarcocystis spp., representing 31.9% of the total samples. Of this total, 55 (82.1%) were identified by PCR-RFLP, using the SspI enzyme, as S. miescheriana and 8 (11.9%) as S. suihominis. Moreover, as contaminants, S. cruzi and S. hominis were detected in 3% of sausage samples. All species were confirmed by nucleotide sequencing. In article 3, as previously mentioned, wild boars may act as possible hosts for species not yet documented circulating in their organisms. Thus, we described the molecular detection of Sarcocystis neurona in tissues from wild boars slaughtered at the Brazil-Uruguay border. Seventy-nine DNA samples were used, subjected to Nested-PCR reactions amplifying the 18SrRNA region, followed by PCR-RFLP with DdeI and HpaII enzymes, 32 samples were positive, corresponding to 40.51% of the total evaluated. Confirmation was also performed with amplification of the ITS1 region and sequencing. However, further studies are needed on the role of these animals as possible hosts and risk factors for transmission to domestic animals.